2020
DOI: 10.2141/jpsa.0190086
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Toll-like Receptor Ligands on the Expression of Proinflammatory Cytokines and Avian <i>β</i>-defensins in Cultured Chick Intestine

Abstract: Few studies have focused on the regulation of cytokine and avian β-defensin (AvBDs) expression for promoting immune defense in the avian intestine. The aim of this study was to investigate the effects of different Toll-like receptor (TLR) ligands (bacterial patterns) on the expression of proinflammatory cytokines (IL-1β and IL-6) and AvBDs (AvBD1, AvBD4, and AvBD7) in the chick intestine. The ileum and cecum of 3-day-old chicks were collected and examined histologically to identity the cells present in the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…The current study revealed that five AvBDs and Cath1 were expressed in the proventriculus and ileum ( Figs. 4 and S1), supporting previous reports ( Mohammed et al, 2015 ; Terada et al, 2018 , 2020c ). We previously reported that ND/IB vaccination did not affect the gene expression of these antimicrobial peptides in the proventriculus, although the levels of some AvBD peptides increased following vaccination ( Yoshimura et al, 2022 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The current study revealed that five AvBDs and Cath1 were expressed in the proventriculus and ileum ( Figs. 4 and S1), supporting previous reports ( Mohammed et al, 2015 ; Terada et al, 2018 , 2020c ). We previously reported that ND/IB vaccination did not affect the gene expression of these antimicrobial peptides in the proventriculus, although the levels of some AvBD peptides increased following vaccination ( Yoshimura et al, 2022 ).…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies in different organisms, including invertebrates (Kurtz, 2005) and mammals (de Bree et al, 2018;Netea et al, 2011Netea et al, , 2020van der Meer et al, 2015), suggested that vaccinations may induce trained innate immunity. The Bacillus Calmette-Guérin vaccine was reported to induce innate immune training by increasing histone modification and cytokine production in immune cells in response to agents unrelated to the vaccine antigen (Kleinnijenhuis et al, 2012(Kleinnijenhuis et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Fourteen AvBDs (AvBD1–14) and 4 cathelicidins (CATH1–3 and CATH-B1) with broad-spectrum antimicrobial activity have been identified ( Hong et al, 2012 ; Wang et al, 2020 ). Regulation of the expression of proinflammatory cytokines and antimicrobial peptides by TLR ligands and pathogenic microbes is reported in the chicken oviduct and other organs ( Cuperus et al, 2013 ; Abdel-Mageed et al, 2014 ; Kamimura et al, 2017 ; Terada et al, 2020b ). Mohammed et al, who examined the effects of LPS and probiotics on the gene expression of antimicrobial peptides in the chick gastrointestinal tract, reported that the expression of AvBD6 and 12 under LPS stimulation was enhanced by probiotics in the proventriculus ( Mohammed and Radey, 2021 ), whereas CATHs expression was not affected ( Mohammed et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…TLR21 recognizes unmethylated CpG-oligodeoxynucleotides (ODN) of bacteria and viruses ( Keestra et al , 2010 ). The expression of TLR 1–5, 7, 15, and 21 in the different intestinal segments has been revealed in chicks ( Mackinnon et al , 2009 ), and the stimulation of TLR ligands modulated the expression of innate immune factors, namely antimicrobial peptides and cytokines in the chick intestine ( Terada et al , 2020 ).…”
Section: Introductionmentioning
confidence: 99%